Inside the Changes in Infoglobo’s Newsroom Routine Eight Years After Integration (Global Journal of Human-Social Science, 2025)
The newsrooms of O Globo Extra and Expresso were unified in 2017 in the so-called Integrated Newsroom aiming to optimize production and expand focus on the digital environment Eight years after the change journalists working in Brazil s largest news company evaluated the advantages and disadvantages of the process As the main disadvantage they pointed to the reduced attention given to newspapers in the so-called popular units In this article we analyze the interviews with the support of authors dedicated to studying the relationship between the accelerated pace of contemporary life and journalism as well as the role of socalled sensation-driven journalism on the internet
Keywords: journalism; integration; changes; internet